Vergleichende historische Religionspädagogik – methodologische Überlegungen - Schröder, Bernd (Zeitschrift für Pädagogik und Theologie, 2016)
This article resumes the state of research in the field of international comparisons regarding the history of Religious Education. After describing a range of purposes to be fulfilled by comparative studies, it categorizes some studies written either in English, French or German according to their methodological approach and subject focus. As a result a three-dimensional map of comparative RE is drawn. The survey turns comparative work out to be of increasing importance within a context of globalization, Europeanization of Education policy and pluralism.